Exchange rate policy and monetary strategy options in the Philippines the search for stability and sustainablity - Houben, Aerdt G. F. J. (United States International Monetary Fund, 1997)
This paper evaluates the Philippines experience with different exchange regimes since 1970. It argues that the shift to a flexible regime was crucial to restoring external viability and generating an export-led economic take-off, but that mixed performance in meeting money targets and asymmetric policy reactions to exchange rate pressures have resulted in an uneven inflation performance. Since adoption of a firm nominal anchor for monetary policy would contribute to a more effective control of inflation and thereby to better prospects for sustained growth, the merits of three monetary strategy options are reviewed: stricter adherence to a money supply rule, adoption of an exchange rate peg, and a switch to direct inflation targeting.
Exchange rate policy and monetary strategy options in the Philippines - the search for stability and sustainability -- Contents -- I. Introduction -- II. The Experience with Different Exchange Regimes -- III. The Monetary Strategy Choice -- IV. Establishing Credibility -- V. Conclusions -- Bibliography.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Foreign exchange rates--Philippines.; Monetary policy--Philippines.; Inflation (Finance)--Philippines.; Sustainable development--Philippines.